Balanced scorecard method as measurement of key performance indicators at PT PELNI (Persero) - Masda Megawati; Nunung Setiyana; Mufti Imam Pekih; Sugeng Santoso (Universitas Mercu Buana, 2021)
PT PELNI (Persero) is engaged in sea transportation and strives to design a comprehensive performance measurement system. The purpose of the research was to identify the indicators used by PT PELNI (Persero) as a measurement of employee performance, draft the concept of a balanced scorecard system in accordance with the measurement of the company's performance, and develop a balanced scorecard simulation design in accordance with the vision, mission, and strategy of PT PELNI (Persero). Measuring the company's performance using the Balanced Scorecard (BSC) method begins with SWOT analysis. This analysis aims to determine internal factors and external factors of the company. From the results of this analysis will be known the current position of the company and what strategies should be applied. The results showed that the company is in good shape, but facing challenges, so the strategy to choose is a diversification strategy. The final result of this study is the selection of several KPIs and 7 (seven) work programs that must be done, including improved efficiency of asset use, promoting cheap tickets during the covid-19 pandemic, efficiency and control utilization during the covid-19 pandemic, developing agency applications and automation of travel service systems, to ensure and monitor On-Time Performance (OTP) per ship, voyage account application development, improving education and training programs for employee self-development.